Analysis of The Influence of Trust on User Satisfaction of Mobile Application E-Commerce Using DeLone and McLean Method - Amani, Nailul; Megawati, Megawati; Maita, Idria; Nur Salisah, Febi; Marsal, Arif (APIC, 2025)
Lazada is one of the mobile-platform based e-commerce that has more than 100 million downloads. Lazada is an e-commerce site that offers several necessities such as mobile phones or tablets; household appliances, health and beauty, men's and women's fashion, baby and children's equipment, and electronics. User satisfaction is one of the important factors in the success of e-commerce implementation. However, there are still many complaints felt by Lazada application users which have an impact on user trust and satisfaction. Therefore, this study aims to determine the level of user satisfaction and how the trust factor influences user satisfaction on the Lazada mobile application using the DeLone& McLean model by adding the trust variable. Respondents in this study were Lazada application users in Pekanbaru City. This study uses a quantitative approach by distributing questionnaires online and sampling using a purposive sampling technique. The total data collected from 100 respondents was analyzed using the PLS-SEM technique with the help of the SmartPLS 4.0 tool. The results of this study indicate that Information Quality, Trust, and Use have a significant influence on user satisfaction and user satisfaction has a significant effect on trust. Of the 10 hypotheses proposed, four were rejected, namely information quality on trust, service quality on user satisfaction, system quality on user satisfaction, and trust on net benefit.